2015
DOI: 10.18483/ijsci.768
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bacteria, Fungi and Protozoa in Three Theobroma Cacao Soils in Ondo State, Nigeria

Abstract: The microbial community of 3 cocoa soils in Ondo State, Nigeria was investigated. Fourteen bacterial isolates, 8 fungi and 9 protozoa were obtained. The bacteria include Actinomyces sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…The result showed that microorganisms (bacteria and fungi) isolated from Cocoa pods were more in infected pods than in healthy pods. The microorganisms isolated from the Cocoa pods is in agreement with the work of Adejumo and Adejoro [27] and Nasril [28].…”
Section: Bibliography Discussionsupporting
confidence: 90%
“…The result showed that microorganisms (bacteria and fungi) isolated from Cocoa pods were more in infected pods than in healthy pods. The microorganisms isolated from the Cocoa pods is in agreement with the work of Adejumo and Adejoro [27] and Nasril [28].…”
Section: Bibliography Discussionsupporting
confidence: 90%